SELF-MEDICATION OF HERBAL MEDICINE FOR WEIGHT LOSS: PHARMACEUTICAL ORIENTATION IN THE DRUGSTORE (REMUNOM, 2023)
Self-medication with phytotherapics for weight loss: pharmaceutical guidance in the pharmacy aimed at understanding the process of obesity and its interference in the search for phytotherapics as a means of losing weight, to identify the risks and benefits associated with the use of phytotherapics for weight loss. weight, to describe the implications of pharmaceutical industry practice for the safe use and appropriate guidance of patients seeking herbal medicines for weight loss. Herbal medicines are widely used in this search for weight loss, since many patients believe that, because they are of "natural" origin, they do not present risks, so they self-medicate. The influence of obesity on this problem was highlighted, analyzing the use of phytotherapics in the process of losing weight and highlighting the importance of pharmaceutical guidance in the drugstore. For this, it was carried out through a qualitative, descriptive investigation, which consisted of a bibliographic review through searches in Google Scholar, Lilacs and SciELO. In view of the discussions presented, it was observed that the process of obesity and its interference in the search for herbal medicines as a way to lose weight are factors that contribute to the problem of self-medication. The ease of access and exposure contribute to its irrational use and without professional guidance, in addition, only the use of phytotherapeutics to lose weight is not effective, since its use must be linked to the practice of physical activities and a balanced diet. However, the use of herbal medicines following the proper recommendations can help in the process of weight loss, bringing many proven effects. The pharmaceutical professional plays a fundamental role in this orientation in the drugstore to reduce self-medication with phytotherapics to lose weight. In the end, it is highlighted that the pharmaceutical orientation in the drugstore when self-medicating with phytotherapics to lose weight is important for the rationalization and prevention of risks in the patient's health. In this way, it is believed that any study that covers this subject contributes to the development of the pharmaceutical professional for all those who need it.